2017
DOI: 10.1016/j.bpsc.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Executive Dysfunction in Autism Spectrum Disorder Is Associated With a Failure to Modulate Frontoparietal-insular Hub Architecture

Abstract: BACKGROUND Comorbid executive dysfunction in autism spectrum disorder (ASD) is a barrier to adaptive functioning, despite remittance of core social-communication symptoms. Network models of ASD address core symptoms but not comorbid executive dysfunction. Following recent demonstrations in healthy adults that, with increasing executive demands, hubs embedded within frontoparietal-insular control networks interact with a more diverse set of networks, we hypothesized that the capability of hubs to do so is pertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 57 publications
2
15
0
1
Order By: Relevance
“…The present analysis extends the findings to the temporal aspect of synchronization: we demonstrate that average fronto-parietal synchronization is higher in ASD, but with more short periods of desynchronization. Research on neuroanatomical structure changes in ASD has previously connected the difficulty of modulating executive control in high-functioning adolescents on autism spectrum to failure of fronto-parietal regions to function as integrative hubs within the brain's network architecture (Lynch et al, 2017). Although the relationships between behavior and oscillatory activity were not tested directly in the present study, some relationships might be hypothesized from prior work, where decreased theta and alpha coherence were shown to lead to impairment in working memory and between-network binding (particularly as related to executive processing, inhibition, and conscious attention), while beta frequency synchrony has been related to successful higher-order cognitive processing (cf.…”
Section: Discussionmentioning
confidence: 99%
“…The present analysis extends the findings to the temporal aspect of synchronization: we demonstrate that average fronto-parietal synchronization is higher in ASD, but with more short periods of desynchronization. Research on neuroanatomical structure changes in ASD has previously connected the difficulty of modulating executive control in high-functioning adolescents on autism spectrum to failure of fronto-parietal regions to function as integrative hubs within the brain's network architecture (Lynch et al, 2017). Although the relationships between behavior and oscillatory activity were not tested directly in the present study, some relationships might be hypothesized from prior work, where decreased theta and alpha coherence were shown to lead to impairment in working memory and between-network binding (particularly as related to executive processing, inhibition, and conscious attention), while beta frequency synchrony has been related to successful higher-order cognitive processing (cf.…”
Section: Discussionmentioning
confidence: 99%
“…95 Diversos estudios concuerdan con que estos síntomas neuropsiquiátricos en adultos con TEA tienen un impacto significativo sobre la función adaptativa y cognitiva, produciendo mayores limitaciones en las AVD. [96][97][98][99] Curiosamente, esta premisa ha sido estudiada en la población general sin TEA, donde la evidencia indica que la depresión promueve el deterioro cognitivo y cuadros demenciales de manera precoz a lo largo del ciclo vital. 100…”
Section: Demencias Y Teaunclassified
“…These changes may emerge early on, given evidence that children and neonates at risk or diagnosed with one of these disorders have dysfunctional hub connectivity (Collin et al, 2017;Lynch et al, 2017;Ray et al, 2014;Shi et al, 2012;Xia et al, 2014). One study using generative network modelling found that differences in functional network topology between patients with childhood onset schizophrenia and healthy controls could be reproduced by tuning the parameters of a generative network model such that the penalty on forming long-range connections was reduced (Vértes et al, 2012).…”
Section: Challenges and Frontiersmentioning
confidence: 99%